Critical role of defect states on visible luminescence from ZnS nanostructures doped with Au, Mn and Ga. (October 2020) - Hafeez, Muhammad; Al-Asbahi, Bandar Ali; Hj Jumali, Mohammad Hafizuddin; Yahaya, Muhammad; Inam, Fakharul; Bhopal, Muhammad Fahad; Bhatti, Arshad S.
Abstract: In this paper, we present the effect of various self doping of catalysts (Au, Mn, and Ga) on the emission properties of cubic ZnS nanostructures. The solubility of the catalysts during the growth was confirmed by FESEM, HRTEM, and XRD. XPS confirmed the formation and variation of intrinsic defects like S, Zn vacancies and extrinsic defects created by self-doped catalysts, which varied with the type of catalysts. The luminescence properties of ZnS nanostructures showed strong dependence on the type of catalyst related defects. Low temperature PL spectroscopy showed that the Au created shallow surface defects states (~100 meV from the conduction band, and Ga induced shallow level defect states with emission in the UV ~360 meV). The temperature dependent PL spectroscopy showed strong negative thermal quenching of PL intensity of blue and orange emission in Au catalyzed ZnS nanostructures while Mn and Ga showed quenching behavior only in yellow and blue bands emission, respectively. Time-resolved PL spectra obtained from all nanostructures demonstrated two time decay constants. The percentage contributions of the fast decay (direct recombination of electrons and holes) and slow decay (trapped electrons at the luminescent sites) were determined for three catalyzed ZnS nanostructures. The percentage contributions and long life time components of blue and green bands were high in Au catalyzed ZnS nanostructures, compared to Mn and Ga catalyzed ZnS nanostructures. Present results indicate the potential use in a broad spectrum tunable nanolasers and multi-color light source.